The "Strange Fruit" of Flannery O'Connor: Damning Monuments in Southern Literature and Southern History - Fannin, Jordan Rowan (Literature and theology, 2021)
This article revisits Flannery O'Connor's racialised Christophany in her short story, "The Artificial N*", in light of contemporary tensions over Confederate monuments in America. It explores her grotesque Christ (manifest in a suburban lawn jockey) that mysteriously acts as a means of grace and effects repentance and reconciliation. It teaches us how to read this racist statuary within the grotesque history of Confederate monuments in the American South. By further situating her story and this history in the matrix of art and community, materiality and memory, her work is able to provide a damning theological critique of the current debate around monument removal, without which we may be content to absent offending sculptures but leave untouched our unreconciled communities and sinful social order.